(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
General Background: Chronic alcoholism poses significant health and social challenges, contributing to increased morbidity, cognitive decline, and social dysfunction. The rising prevalence of alcohol dependence necessitates a comprehensive approach to treatment and rehabilitation. Specific Background: In Uzbekistan, the incidence of alcohol dependence has grown considerably, while access to specialized treatment remains limited due to social stigma and inadequate infrastructure. Despite the availability of emergency medical services for acute intoxication, long-term rehabilitation remains underdeveloped. Knowledge Gap: While detoxification and pharmacological treatments are well-documented, there is a lack of effective psychosocial rehabilitation programs tailored to chronic alcoholics. The integration of psychological interventions, social support, and cognitive rehabilitation is crucial but remains underexplored. Aims: This study examines current approaches to alcohol addiction treatment, emphasizing the necessity of psychosocial rehabilitation in addition to medical detoxification. Results: The findings highlight the shortcomings of existing emergency medical care, which primarily focuses on immediate stabilization rather than long-term recovery. The introduction of psychosocial interventions, such as motivational interviewing, cognitive-behavioral therapy, and family-based support, is essential to improve rehabilitation outcomes. Novelty: The study emphasizes the need for a holistic rehabilitation model combining medical, psychological, and social interventions to address alcohol dependence effectively. Implications: The findings underscore the importance of integrating psychosocial therapy into Uzbekistan’s healthcare system to reduce relapse rates and improve patients’ long-term well-being. Future research should focus on developing structured rehabilitation protocols that combine pharmacological treatment with cognitive and social support interventions for sustained recovery.